Dinuclear gold(I)‐N‐heterocyclic carbene complexes: Synthesis, characterization, and catalytic application for hydrohydrazidation of terminal alkynes. (23rd July 2020) - Yadav, Seema; Ray, Sriparna; Singh, Ajeet; Mobin, Shaikh M.; Roy, Tapta Kanchan; Dash, Chandrakanta
Abstract : Dinuclear gold(I)‐N‐heterocyclic carbene complexes were developed for the hydrohydrazidation of terminal alkynes. The gold(I)‐N‐heterocyclic carbene complexes 2a‐2b were synthesized in good yields from silver complexes synthesized in situ, which in turn were obtained from the corresponding imidazolium salts with Ag2 O in dichloromethane as a solvent. The new air‐stable gold(I)‐NHC complexes, 2a ‐2b, were characterized using NMR spectroscopy, elemental analysis, infrared, and mass spectroscopy studies. The gold(I) complex 2a was characterized using X‐ray crystallography. Bis ‐N‐heterocyclic carbene–based gold(I) complexes 2a ‐2b exhibited excellent catalytic activities for hydrohydrazidation of terminal alkynes yielding acylhydrazone derivatives. The working catalytic system can be used in gram‐scale synthesis. In addition, the catalytic reaction mechanism of the hydrohydrazidation of terminal alkynes by gold(I)‐NHC complex was studied in detail using density functional theory. Abstract : Air‐ and moisture‐stable dinuclear gold‐N‐heterocyclic carbene complexes were synthesized and characterized. The dinuclear gold(I)‐NHC complexes were successfully used as a catalyst for the hydrohydrazidation of terminal alkynes. The catalytic reaction mechanism was investigated using density functional theory.